2005
DOI: 10.1007/s10482-005-7283-3
|View full text |Cite
|
Sign up to set email alerts
|

Yeast population dynamics of industrial fuel-ethanol fermentation process assessed by PCR-fingerprinting

Abstract: Yeast populations used in industrial production of fuel-ethanol may vary according to the plant process conditions and to the environmental stresses imposed on yeast cells. Therefore, yeast strains isolated from a particular industrial process may be adapted to such conditions and should be used as the starter strain instead of less adapted commercial strains. This work reports the use of a PCR-fingerprinting method based on microsatellite primer (GTG) 5 to characterize the yeast population dynamics during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…4a clearly show that the selected yeast strains successfully compete with baker's yeast, commencing from such a disproportional biomass ratio at the start of fermentation (0.5 kg of selected yeast strains vs. 1 ton of baker's yeast; in some distilleries, even 12 tons). Nevertheless, Silva-Filho et al (2005) found that a yeast cell PCR-fingerprint profile (P18) was dominant in cane juice-fermenting distilleries, while P6 and P1A profiles were dominant in molasses medium. 4b.…”
Section: The Yeast Population Dynamics In Industrial Fermentationsmentioning
confidence: 98%
See 1 more Smart Citation
“…4a clearly show that the selected yeast strains successfully compete with baker's yeast, commencing from such a disproportional biomass ratio at the start of fermentation (0.5 kg of selected yeast strains vs. 1 ton of baker's yeast; in some distilleries, even 12 tons). Nevertheless, Silva-Filho et al (2005) found that a yeast cell PCR-fingerprint profile (P18) was dominant in cane juice-fermenting distilleries, while P6 and P1A profiles were dominant in molasses medium. 4b.…”
Section: The Yeast Population Dynamics In Industrial Fermentationsmentioning
confidence: 98%
“…For example, some distilleries start with 1-12 tons of pressed baker's yeast. More recently, Silva-Filho et al (2005) demonstrated, by PCR-fingerprinting of yeast samples from six distilleries, that indigenous strains could be more adapted to the industrial process than commercial ones, also identifying dominant strains. It was also observed that only a wild strain (JA-1) previously isolated from one distillery could survive the recycling process, and in most of the distilleries a succession of different indigenous S. cerevisiae strains performed the industrial fermentation (Basso et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Their enzymes provide interesting wine organoleptic characteristics (Charoenchai and others ). Moreover, these enzymes are interesting in biotechnology, for use in food processing such as cheese, pickles, or sausage (Da Silva‐Filho and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation process for industrial fuel alcohol production is a complex environment involving a frequent succession of different yeast strains and species (Silva‐Filho et al. 2005a; Basílio et al.…”
Section: Introductionmentioning
confidence: 99%
“…The industrial strain JP1 was isolated based on its capacity to dominate industrial fermentation processes (Silva‐Filho et al. 2005a,b).…”
Section: Introductionmentioning
confidence: 99%